Specific Capacitance Characteristics of Carbons, Activated by Potassium Hydroxide - Budzulyak, I. M.; Rachiy, B. I.; Vashchynsky, V. M.; Berkeschuk, M. V. (Physics and Chemistry of Solid State, 2015)
This work is devoted to the study of the charge accumulation in the electric double layer on the polarized electrode of the electrochemical systems. A series of samples of the nanoporous carbon material obtained from natural raw materials. In order to improve its performance it has been made the modification of porous structure of the samples by thermal and chemical treatment. As an activator potassium hydroxide was used. Determination of the specific characteristics of ultracapacitors was conducted in a two-electrode cells by potentiodynamic and galvanostatic methods. The pore formation process was studied by simultaneous thermoanalyzer STA 449 F3 Jupiter. It is shown that the resulting materials have high values of capacitance, which is realized by charge accumulation in the electric double layer, the pseudocapacitance contribution is absent. The optimal modes of carbonization and chemical activation were defined. The dependence of specific characteristics on the modification mode has explained. It is shown that almost all the samples are highly resistant in a wide range of current densities.